Identification and characterization of novel lineage 1 Powassan virus strains in New York State. Issue 1 (31st December 2023) - Lange, Rachel E.; Dupuis II, Alan P.; Prusinski, Melissa A.; Maffei, Joseph G.; Koetzner, Cheri A.; Ngo, Kiet; Backenson, Bryon; Oliver, JoAnne; Vogels, Chantal B.F.; Grubaugh, Nathan D.; Kramer, Laura D.; Ciota, Alexander T.
ABSTRACT: Powassan virus (POWV, family Flaviviridae ) is a reemerging tick-borne virus endemic in North America and Russia. In 1997, a POWV-like agent was isolated from Ixodes scapularis in New England and determined to be genetically distinct from the original POWV isolate. This revealed the existence of two lineages: lineage 1, prototype Powassan virus (POWV-1) and lineage 2, deer tick virus (DTV). POWV-1 is thought to be primarily maintained in a cycle between I. cookei and woodchucks and I. marxi and squirrels, while DTV is primarily maintained in a cycle between I. scapularis and small mammal hosts. Recent tick, mammalian, and human isolates from New York State (NYS) have been identified as DTV, but for the first time in 45 years, we detected four POWV-1 isolates, including the first reported isolation of POWV-1 from I. scapularis . We aimed to investigate genotypic and phenotypic characteristics of recent NYS isolates through sequence analysis and evaluation of replication kinetics in vitro and in vivo . Our sequencing revealed genetic divergence between NYS POWV-1 isolates, with two distinct foci. We found that POWV-1 isolates displayed variable replication kinetics in nymphal ticks but not in cell culture. POWV-1 isolated from I. scapularis displayed increased fitness in experimentally infected I. scapularis as compared to historic and recent POWV-1 isolates from I. cookei . These data suggest the emergence of divergent POWV-1 strains in alternate tick hosts and maintenance of genetically and phenotypically discrete POWV-1 foci.